Early Passage Mesenchymal Stem Cells Display Decreased Radiosensitivity and Increased DNA Repair Activity - Wu, Po‐Kuei (Stem Cells Transl Med, 2017)
Cell therapies using human mesenchymal stem cells (MSCs) have received much attention in the past decade. In pursuit of the therapeutic potential of MSCs, cell expansion is required to generate a great number of cells with desired phenotype and functionality. Long‐term expansion in vitro, however, can lead to altered functions. To explore the changes in DNA damage responses (DDR) in MSCs expanded, DDR pathways following irradiation were characterized in early‐ and late‐passage bone marrow MSCs. Seventy‐two hours after irradiation, the percentage of sub‐G1 cells in early‐passage MSCs did not change significantly. Reduced TUNEL staining was observed in early‐passage MSCs compared to late‐passage MSCs 4 h after irradiation. Comet assay also revealed that early‐passage MSCs were more resistant to irradiation or DNA damages induced by genotoxic agents than late‐passage MSCs. ATM phosphorylation and γ‐H2AX and phospho‐p53 increased in early‐passage MSCs while decreased in late‐passage MSCs. Through inhibition by KU55933, DDR pathway in early‐passage MSCs was shown to be ATM‐dependent. Higher levels of poly (ADP‐ribose) polymerase‐1 (PARP‐1) and PAR synthesis were observed in early‐passage MSCs than in late‐passage MSCs. Knockdown of PARP‐1 in early‐passage MSCs resulted in sensitization to irradiation‐induced apoptosis. Overexpression of PARP‐1 in late passage MSCs could render irradiation resistance. Lower activity of DDR in late‐passage MSCs was associated with rapid proteasomal degradation of PARP‐1. In conclusion, early‐passage MSCs are more irradiation‐resistant and have increased DDR activity involving PARP‐1, ATM and their downstream signals. Stem Cells Translational Medicine 2017;6:1504–1514